Tough and Water‐Insensitive Self‐Healing Elastomer for Robust Electronic Skin - Kang, Jiheong; Son, Donghee; Wang, Ging‐Ji Nathan; Liu, Yuxin; Lopez, Jeffrey; Kim, Yeongin; Oh, Jin Young; Katsumata, Toru; Mun, Jaewan; Lee, Yeongjun; Jin, Lihua; Tok, Jeffrey B.‐H.; et al. (Advanced materials (Weinheim), 2018)
An electronic (e‐) skin is expected to experience significant wear and tear over time. Therefore, self‐healing stretchable materials that are simultaneously soft and with high fracture energy, that is high tolerance of damage or small cracks without propagating, are essential requirements for the realization of robust e‐skin. However, previously reported elastomers and especially self‐healing polymers are mostly viscoelastic and lack high mechanical toughness. Here, a new class of polymeric material crosslinked through rationally designed multistrength hydrogen bonding interactions is reported. The resultant supramolecular network in polymer film realizes exceptional mechanical properties such as notch‐insensitive high stretchability (1200%), high toughness of 12 000 J m−2, and autonomous self‐healing even in artificial sweat. The tough self‐healing materials enable the wafer‐scale fabrication of robust and stretchable self‐healing e‐skin devices, which will provide new directions for future soft robotics and skin prosthetics. An extremely tough and water‐insensitive self‐healing elastomer crosslinked through multistrength hydrogen bonding interactions is described. The resultant crosslinking network in polymer film realizes exceptional mechanical properties such as notch‐insensitive high stretchability (1200%), a high toughness of 12 000 J m−2, and autonomous self‐healing even in artificial sweat. The tough self‐healing materials enable the wafer‐scale fabrication of robust and stretchable self‐healing e‐skin devices.